Letters written during a short residence in Spain and Portugal - Southey, Robert, 1774-1843, author.
1 online resource
Keywords: In 1797 Robert Southey published a richly detailed account of his journey in Spain and Portugal between December 1795 and May 1796, from his arrival in Coruna in the northwest of the Spanish coast to the heart of Castile and into Madrid, before making his way to Lisbon. Structured as a series of letters written as he travelled across the Iberian Peninsula, Letters Written During a Short Residence in Spain and Portugal engages with the tradition of English travelogues, while borrowing traits from other genres such as the journal, translation, literary criticism, history, and the picturesque guidebook. On his way, Southey comments on every aspect of Spanish and Portuguese society, from local food and wine, bizarre customs, literature and theatregoing, to Iberian politics and religion. In his letters Southey, who would grow to become one of the leading Hispanists in late Georgian England, contrasts the political, religious, cultural and social systems of Britain and two of the oldest nations in the European continent in a way that raises important questions about cultural contact and transmission during the Romantic period. This edition critically reassesses Letters Written During a Short Residence in Spain and Portugal by looking at Southey's deeply ambiguous cultural cosmopolitanism and his life-long investment in all things Spanish and Portuguese.